2020
DOI: 10.1111/ases.12851
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic is a safe and feasible option for uncomplicated appendicitis in pregnancy ‐ A retrospective cohort study

Abstract: Introduction Acute appendicitis is the commonest surgical emergency during pregnancy. The aim of this study is to evaluate the outcomes between antibiotic therapy and appendectomy in the management of uncomplicated appendicitis during gestation. Methods From January 2015 to April 2019, there were 2174 emergency appendicitis diagnosed in the University of Hong Kong‐Shenzhen Hospital. Among them, 54 pregnant women were diagnosed with acute uncomplicated appendicitis and the clinical records were reviewed. Clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 17 publications
(17 reference statements)
0
27
0
1
Order By: Relevance
“…Our study showed that NST was associated with lower risk of preterm labor by 60% as compared with OA, but no difference in abortion and cesarean section between NST and OA treatments was seen. Although some previous studies suggested that conservative treatment of AA in pregnant women achieved satisfactory pregnancy outcomes, these patients normally had relatively mild conditions [ 4 ]. The World Society of Emergency Surgery guidelines note that no evidence supports superior performance of conservative treatment in pregnancy outcomes, as compared with surgical treatments [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study showed that NST was associated with lower risk of preterm labor by 60% as compared with OA, but no difference in abortion and cesarean section between NST and OA treatments was seen. Although some previous studies suggested that conservative treatment of AA in pregnant women achieved satisfactory pregnancy outcomes, these patients normally had relatively mild conditions [ 4 ]. The World Society of Emergency Surgery guidelines note that no evidence supports superior performance of conservative treatment in pregnancy outcomes, as compared with surgical treatments [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have assessed the association of laparoscopy with adverse pregnancy outcomes, particularly with fetal loss, preterm birth, and cesarean section. While a significantly lower risk of preterm birth was found in patients treated by LA than OA [ 22 ], other studies found no difference in preterm birth between the two surgical approaches [ 2 , 3 , 4 ], and few studies found that LA was associated with increased risk of fetal loss [ 6 , 22 24 ]. A case–control study reported that LA during pregnancy was associated with an increased rate of cesarean delivery [ 12 ], while other studies found that the risk of cesarean delivery for LA and OA treatments was comparable [ 6 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study from China to see the association between antibiotics and complication rate among 54 pregnant women showed that the patients with antibiotics ( n = 34) experienced no complications. However, recurrence occurred in the conservative group in one patient during pregnancy and two patients after delivery, treated with appendectomy [ 35 ]. In our data, complicated appendicitis was 25% in pregnant vs. 9% in nonpregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged exposure to anesthesia can have an adverse effect. The mean operating time of LA is 45 minutes (range: 10–70 minutes) [ 17 , 18 , 27 , 32 , 35 , 36 ]. In our data, the average time did not differ in the two groups, with a mean of 50 minutes.…”
Section: Discussionmentioning
confidence: 99%